CONTRIBUTION OF T.D. ZYRYANOVA TO THE STUDY OF THE PROBLEM OF PELVIC BONES INJURIES AND ASSOCIATED COMPLICATIONS - Z. V. Koshkareva; V. A. Sorokovikov; M. A. Makarova (Acta Biomedica Scientifica)
The article presents the results of scientific fundamental and applies researches of Tatyana Dmitrievna Zyryanova on the problem of study of pelvic bones and coxal cavity fractures complicated and non-complicated with bladder, urethra and rectum injuries. T.D. Zyryanova studied and systematized problems on the statistics of this incapacitating pathology, its clinic and diagnostics. She determined indications for conservative and surgical treatment of certain pelvic bones and pelvic waist injury and an algorithm of rehabilitation measures after the treatment. T.D. Zyryanova and co-authors proposed system of transport immobilization at the injuries of pelvic bones and concomitant injuries of internals of cavity of the lesser pelvis.